A Medium Frequency Wireless Communication System For Underground Mines (de44866e-7403-4d05-a8a8-659dd3603d13) - Larry G. Stolarczyk (The National Institute for Occupational Safety and Health (NIOSH), 1984)
This report deals with information regarding a new Medium Frequency (MF) Wireless Communication System for underground mines. This new telecommunication system works on low loss electromagnetic wave propagation modes which allow it to provide quality radio communications almost anywhere in a mine. Tests show the MF system can provide improved safety and managerial control, increased productivity, better organizational team-work and reduced maintenance cost; furthermore, MF's unique design allows for easy installation at a minimum cost. This paper covers the following: 1) MF design plan, 2) Overview of mine radio communications systems, 3) Preparations needed for designing an MF system, 4) MF equipment, 5) MF installation, 6) MF design considerations, 7) MF design specifica¬tions, and 8) Recommendations dealing with MF system. Experiments in four mines are illustrated to demonstrate the success and via¬bility of the MF system. The mines range from small (500 tons/day) to large (67,000 tons/day) capacity and represent several different mining methods. The MF Wireless Communication System represents an advancement in mining communication and the groundwork for other advanced mine systems.